Adaptive intelligent-estimation-based tracking controller design strategy for switched nonlinear systems with unmodeled dynamics and an output constraint. (August 2022) - Yin, Yutong; Niu, Ben; Liu, Xiaomei; Wang, Xinjun; Jiang, Xiaoli
Abstract: This paper focuses on the intelligent-estimation-based tracking controller design problem for a class of switched non-lower triangular nonlinear systems with unmodeled dynamics and an output constraint. It should be pointed out that the design process of controller is quite difficult due to the existence of unmodeled dynamics and switched events in the system, hence some sophisticated and delicate mathematical theories and design techniques need to be adopted. In our proposed design procedure, the structural feature of Gaussian functions is utilized to conquer the obstruction of nonstrict-feedback form. Furthermore, the difficulties resulted from the unmodeled dynamics are solved by the established dynamic signal Based on the above technical algorithm, the results can be obtained as follows: (a) All signals in the switched closed-loop system are bounded. (b) The output of the system fluctuates in a small neighborhood near the reference signal without the violation of the output constraint. Finally, the simulation results are provided to verify the potency of the developed approach.